Biochemical characterisation of alpha-amylase inhibitors from achyranthes aspera and their interactions with digestive amylases of coleopteran and lepidopteran insects - Hivrale, Vandana K.; Chougule, Nanasaheb P.; Giri, Ashok P.; Chhabda, Pavan J.; Kachole, Andmanvendra S. (Journal of the Science of Food and Agriculture, 2011)
BACKGROUND: Starchy seeds are an important food and a source of dietary ingredients in many countries. However, they suffer from extensive predation by bruchids (weevils) and other pests. alpha-Amylase inhibitors are attractive candidates for the control of seed weevils, as these insects are highly dependent on starch as an energy source. RESULTS: A proteinaceous alpha-amylase inhibitor from the seeds of Achyranthes aspera was identified, purified and characterised. In electrophoretic analysis, two prominent amylase inhibitor activity bands (AI1 and AI2) were detected. The inhibitor was purified 9.99-fold with 1206.95 total amylase inhibitor units mg(-1) protein. The molecular weight of the purified inhibitor was around 6 kDa. The isolated alpha-amylase inhibitor was found to be resistant to heat and proteolysis. Feeding analysis of Callosobruchus maculatus larvae on a diet containing seed powder of A. aspera revealed that survival of the larvae was severely affected, with the highest mortality rate occurring on the fifth day of feeding. The isolated inhibitor inhibited the majority of amylase isoforms of C. maculatus, Tribolium confusum and Helicoverpa armigera in electrophoretic analysis and solution assays. CONCLUSION: The information obtained in the present investigation could be useful for a genetic engineering approach that would make seeds resistant to storage pest infestations. (C) 2011 Society of Chemical Industry
Keywords: Achyranthes aspera; Amylase inhibitors; amylases; Callosobruchus maculatus; Tribolium confusum

Biosynthesis of antinutritional alkaloids in solanaceous crops is mediated by clustered genes - Itkin, M.; Heinig, U.; Tzfadia, O.; Bhide, Amey J.; Shinde, B.; Cardenas, Pablo D.; Bocobza, S. E.; Unger, T.; Malitsky, Sergey; Finkers, R.; Tikunov, Y.; Bovy, A.; et al. (Science, 2013)
Steroidal glycoalkaloids (SGAs) such as alpha-solanine found in solanaceous food plants-as, for example, potato-are antinutritional factors for humans. Comparative coexpression analysis between tomato and potato coupled with chemical profiling revealed an array of 10 genes that partake in SGA biosynthesis. We discovered that six of them exist as a cluster on chromosome 7, whereas an additional two are adjacent in a duplicated genomic region on chromosome 12. Following systematic functional analysis, we suggest a revised SGA biosynthetic pathway starting from cholesterol up to the tetrasaccharide moiety linked to the tomato SGA aglycone. Silencing GLYCOALKALOID METABOLISM 4 prevented accumulation of SGAs in potato tubers and tomato fruit. This may provide a means for removal of unsafe, antinutritional substances present in these widely used food crops.

Biochemical, structural and functional diversity between two digestive alpha-amylases from helicoverpa armigera - Bhide, Amey J.; Channale, Sonal M.; Patil, Sucheta S.; Gupta, Vidya S.; Ramasamy, Sureshkumar; Giri, Ashok P. (Biochimica Et Biophysica Acta-General Subjects, 2015)
Background: Helicoverpa armigera (Lepidoptera) feeds on various plants using diverse digestive enzymes as one of the survival tool-kit. The aim of the present study was to understand biochemical properties of recombinant alpha-amylases of H. armigera viz., HaAmy1 and HaAmy2. Methods: The open reading frames of HaAmy1 and HaAmy2 were cloned in Pichia pastoris and expressed heterologously. Purified recombinant enzymes were characterized for their biochemical and biophysical attributes using established methods. Results: Sequence alignment and homology modeling showed that HaAmy1 and HaAmy2 were conserved in their amino acid sequences and structures. HaAmy1 and HaAmy2 showed optimum activity at 60 degrees C; however, they differed in their optimum pH. Furthermore, HaAmy2 showed higher affinity for starch and amylopectin whereas HaAmy1 had higher catalytic efficiency. HaAmy1 and HaAmy2 were inhibited to the same magnitude by a synthetic amylase inhibitor (acarbose) while wheat amylase inhibitor showed about 2-fold higher inhibition of HaAmy1 than HaAmy2 at pH 7 while 6-fold difference at pH 11. Interactions of HaAmy1 and HaAmy2 with wheat amylase inhibitor revealed 2:1 stoichiometric ratio and much more complex interaction with HaAmy1. Conclusions: The diversity of amylases in perspective of their biochemical and biophysical properties, and their differential interactions with amylase inhibitors signify the potential role of these enzymes in adaptation of H. armigera on diverse plant diets. General significance: Characterization of digestive enzymes of H. armigera provides the molecular basis for the polyphagous nature and thus could assist in designing future strategies for the insect control. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: alpha-amylases; Amylase inhibitors; Digestive enzymes; Enzyme activity; Helicoverpa armigera

Bio-physical evaluation and in vivo delivery of plant proteinase inhibitor immobilized on silica nanospheres - Khandelwal, Neha; Doke, Dhananjay S.; Khandare, Jayant J.; Jawale, Priyanka V.; Biradar, Ankush V.; Giri, Ashok P. (Colloids and Surfaces B-Biointerfaces, 2015)
Recombinant expression of Capsicum annuum proteinase inhibitors (CanPI-13) and its application via synthetic carrier for the crop protection is the prime objective of our study. Herein, we explored proteinase inhibitor peptide immobilization on silica based nanospheres and rods followed by its pH mediated release in vitro and in vivo. Initial studies suggested silica nanospheres to be a suitable candidate for peptide immobilization. Furthermore, the interactions were characterized biophysically to ascertain their conformational stability and biological activity. Interestingly, bioactive peptide loading at acidic pH on nanospheres was found to be 62% and showed 56% of peptide release at pH 10, simulating gut milieu of the target pest Helicoverpa armigera. Additionally, in vivo study demonstrated significant reduction in insect body mass (158 mg) as compared to the control insects (265 mg) on 8th day after feeding with CanPI-13 based silica nanospheres. The study confirms that peptide immobilized silica nanosphere is capable of affecting overall growth and development of the feeding insects, which is known to hamper fecundity and fertility of the insects. Our study illustrates the utility and development of peptide-nanocarrier based platform in delivering diverse biologically active complexes specific to gut pH of H. armigera. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Biodelivery; Helicovera armigera; Protein `corona'; Proteinase inhibitor; Silica nanospheres

Budding trends in integrated pest management using advanced micro- and nano-materials: challenges and perspectives - Khandelwal, Neha; Barbole, Ranjit S.; Banerjee, Shashwat S.; Chate, Govind P.; Biradar, Ankush V.; Khandare, Jayant J.; Giri, Ashok P. (Journal of Environmental Management, 2016)
One of the most vital supports to sustain human life on the planet earth is the agriculture system that has been constantly challenged in terms of yield. Crop losses due to insect pest attack even after excessive use of chemical pesticides, are major concerns for humanity and environment protection. By the virtue of unique properties possessed by micro and nano-structures, their implementation in Agri-biotechnology is largely anticipated. Hence, traditional pest management strategies are now forestalling the potential of micro and nanotechnology as an effective and viable approach to alleviate problems pertaining to pest control. These technological innovations hold promise to contribute enhanced productivity by providing novel agrochemical agents and delivery systems. Application of these systems engages to achieve: i) control release of agrochemicals, ii) site-targeted delivery of active ingredients to manage specific pests, iii) reduced pesticide use, iv) detection of chemical residues, v) pesticide degradation, vi) nucleic acid delivery and vii) to mitigate post-harvest damage. Applications of micro and nano-technology are still marginal owing to the perception of low economic returns, stringent regulatory issues involving safety assessment and public awareness over their uses. In this review, we highlight the potential application of micro and nano-materials with a major focus on effective pest management strategies including safe handling of pesticides. (C) 2016 Elsevier Ltd. All rights reserved.

Biosynthesis and tissue-specific partitioning of camphor and eugenol in Ocimum kilimandscharicum - Singh, Priyanka; Kalunke, Raviraj M.; Shukla, Anurag; Tzfadia, Oren; Thulasiram, V. Hirekodathakallu; Giri, Ashok P. (Phytochemistry, 2020)
In Ocimum kilimandscharicum, the relative volatile composition of camphor in leaves was as high as 55%, while that of eugenol in roots was 57%. These metabolites were differentially partitioned between the aerial and root tissues. Global metabolomics revealed tissue-specific biochemical specialization, evident by the differential distribution of 2588 putative metabolites across nine tissues. Next-generation sequencing analysis indicated differential expression of 51 phenylpropanoid and 55 terpenoid pathway genes in aerial and root tissues. By integrating metabolomics with transcriptomics, the camphor biosynthesis pathway in O. kilimandscharicum was elucidated. In planta bioassays revealed the role of geranyl diphosphate synthase (gpps) and borneol dehydrogenase (bdh) in camphor biosynthesis. Further, the partitioning of camphor was attributed to tissue-specific gene expression of both the pathway entry point (gpps) and terminal (bdh) enzyme. Unlike camphor, eugenol accumulated more in roots; however, absence of the eugenol synthase gene in roots indicated long distance transport from aerial tissues. In silico co-expression analysis indicated the potential involvement of ATP-binding cassette, multidrug and toxic compound extrusion, and sugar transporters in eugenol transport. Similar partitioning was evident across five other Ocimum species. Overall, our work indicates that metabolite partitioning maybe a finely regulated process, which may have implications on plant growth, development, and defense.
Keywords: Borneol dehydrogenase; Camphor; Eugenol; Geranyl diphosphate synthase; Lamiaceae; Metabolite partitioning; Metabolomics; Ocimum kilimandscharicum; Transcriptomics

BAHD-type acyltransferase concludes the biosynthetic pathway of non-bitter glycoalkaloids in ripe tomato fruit - Sonawane, Prashant D.; Gharat, Sachin A.; Jozwiak, Adam; Barbole, Ranjit; Heinicke, Sarah; Almekias-Siegl, Efrat; Meir, Sagit; Rogachev, Ilana; O'Connor, Sarah E.; Giri, Ashok P.; Aharoni, Asaph (Nature Communications, 2023)
During tomato fruit ripening, bitter and toxic steroidal glycoalkaloids (SGAs) are converted to nonbitter and less toxic forms, but proposed acylating enzyme in pathway remain unknown. Here, authors report BAHD-type acyltransferase that catalyze acylation step in biosynthesis of non-bitter SGAs in tomato. Tomato is the highest value fruit and vegetable crop worldwide, yet produces & alpha;-tomatine, a renowned toxic and bitter-tasting anti-nutritional steroidal glycoalkaloid (SGA) involved in plant defense. A suite of modifications during tomato fruit maturation and ripening converts & alpha;-tomatine to the non-bitter and less toxic Esculeoside A. This important metabolic shift prevents bitterness and toxicity in ripe tomato fruit. While the enzymes catalyzing glycosylation and hydroxylation reactions in the Esculeoside A pathway have been resolved, the proposed acetylating step remains, to date, elusive. Here, we discovered that GAME36 (GLYCOALKALOID METABOLISM36), a BAHD-type acyltransferase catalyzes SGA-acetylation in cultivated and wild tomatoes. This finding completes the elucidation of the core Esculeoside A biosynthetic pathway in ripe tomato, allowing reconstitution of Esculeoside A production in heterologous microbial and plant hosts. The involvement of GAME36 in bitter SGA detoxification pathway points to a key role in the evolution of sweet-tasting tomato as well as in the domestication and breeding of modern cultivated tomato fruit.